Impact of COVID-19 and Macroeconomic Factors on Sharia Stock Market Performance: A Case Study of Indonesia - Aam; Dito (SMART Insight, 2021)
Macroeconomic variables strongly influence investment decisions because macroeconomic variables can affect the stock market according to the country's economic conditions and government policies. The Covid-19 pandemic has harmed the economy of almost all countries in the world, including Indonesia. This study explores the effect of Covid-19 and various macroeconomic variables on Islamic stock prices in Indonesia, namely the Jakarta Islamic Index (JII), by analyzing monthly data from 2015 to 2020. This study uses the Vector Error Correction Model (VECM) to investigate the short-term and long-term effects of each macroeconomic variable and international stock index to the JII index. The results showed that the Covid-19 dummy variable significantly impacts the JII index in the short term. Meanwhile, inflation, exchange rates, money supply, the United States S&P 500 index, China's SSE index, and the Covid-19 dummy variable significantly affect the JII index in the long term. Long-term results show that inflation, exchange rates, the United States S&P 500 index, and the Covid-19 dummy variable harm the JII index. On the other hand, the money supply and China's SSE Index positively affect the JII index. This study confirms that Covid-19 can affect the decline in the Islamic stock index in Indonesia, at least the results of this study can be used as material for discussion and research on the economic impact of the Covid-19 pandemic by providing empirical evidence that the pandemic has a restrictive effect on the performance of the Islamic stock market in Indonesia.